The colonial politics of British publishing: Revisiting Matiel Mogannam’s (1937) The Arab Woman and the Palestine Problem - Mariam A. Karim (22997161) (2025)
Colonial gatekeeping in the Anglo-publishing industry has affected Palestinian voices for more than 80 years. In 1936, Palestinian American Matiel Mogannam’s book, The Arab Woman and the Palestine Problem (1937) was rejected by the English publishing house Routledge & Sons as “propaganda” on the advice of former British military officer and noted Zionist figure Norman Bentwich. The Arab Woman and the Palestine Problem is considered the first book written in English that traces the history of the Arab and Palestinian women’s movements in the context of the Palestinian national liberation struggle. This article critiques and debunks Bentwich’s accusations using Mogannam’s writing on the topic of women’s anti-colonial history. It demonstrates that Mogannam’s book was rejected because of its mobilizing potential and that Mogannam’s efforts paved the way for Palestine solidarity in the English-speaking world. Other Information Published in: Communication, Culture & Critique License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/ccc/tcaf034